Florística, estrutura fitossociológica e produção de serapilheira do manguezal do rio São Francisco - Santos, Tiago de Oliveira (2013)
This Master's Thesis presents the results of research conducted under the Project ASSESSMENT OF POTENTIAL AS SEQUESTRANT MANGROVE FORESTS CARBON - UFRJ / UFS / UERJ (Case Study of Mangrove Forest River Estuarine Region of San Francisco - Sergipe / Alagoas), with the support of the Erosion and Sedimentation Laboratory, part of the Department of Agricultural Engineering, Federal University of Sergipe. The environmental liabilities created on account of unsustainable use of natural resources over the years has been suppressing and / or degrading a significant portion of mangroves due to the disorderly occupation and exploitation of their areas. Thus, gathering information on vegetation structure becomes a valuable tool for understanding the current state of the same. In this context, the objective of this study was to characterize the floristic, phytosociological structure and litterfall of the mangrove estuary of the river São Francisco, Sergipe. This action will provide a structural description of the community of mangrove trees and shrubs and the factors that promote change in these communities. The results show that the mangrove river São Francisco present a heterogeneous development, presenting higher in the intermediate region of the estuary, where there is less influence of anthropogenic impacts. We recorded species: schaueriana Avicennia, Avicennia germinans, Laguncularia racemosa, Conocarpus erectus and Rhizophora mangle. The average height of forests ranged from 2.88 to 15.63 m, the DBH 3.95 to 19.74 cm, basal area, live from 4.22 to 47.83 m2.ha-1 and density logs Live 375-9100 trunks.ha-1. The annual litter production was 274.43 t.ha-1.year-1 in the first year and 267.92 t.ha-1.year-1 in the second year. Generally, litter production, per compartment, submitted the following descending order: Leaves > Twigs and Branches > Stipules > Fruits and Propagating Material > Miscellaneous > Flowers. Tensors identified in the estuary, the largest impacts are promoting marine erosion and human activities, both promote the removal of large areas.